2020
DOI: 10.1101/2020.04.02.020891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational prediction of Drug-Disease association based on Graph-regularized one bit Matrix completion

Abstract: MotivationInvestigation of existing drugs is an effective alternative to discovery of new drugs for treating diseases. This task of drug re-positioning can be assisted by various kinds of computational methods to predict the best indication for a drug given the open-source biological datasets. Owing to the fact that similar drugs tend to have common pathways and disease indications, the association matrix is assumed to be of low-rank structure. Hence, the problem of drug-disease association prediction can been… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…• Graph regularized frameworks (GRMF: graph regularized matrix factorization [20], GRMC: graph regularized matrix completion [39], GRBMC: graph regularized binary matrix completion [37])…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Graph regularized frameworks (GRMF: graph regularized matrix factorization [20], GRMC: graph regularized matrix completion [39], GRBMC: graph regularized binary matrix completion [37])…”
Section: Resultsmentioning
confidence: 99%
“…The minimization with respect to X can be solved by making use of the PPXA (parallel proximal algorithm) [44]. Such approach allows to decouple the constraints by introducing proxy variables and then solving each subproblem in a parallel fashion as shown in [37] (referred as GRBMC here).…”
Section: Graph Regularized Matrix Completion (Grmc)mentioning
confidence: 99%
“…• Drug Disease association prediction: One predicts the probability that a certain drug will interact with a disease or not in a partially filled drug-disease association matrix. [84,46,81,48].…”
Section: Modeling Biological Interactionsmentioning
confidence: 99%
“…It was found that graph regularised techniques, including similarities based on genomic structure of viruses and chemical structure of antiviral drugs, performed better than the non-regularised competitors. The most successful techniques were graph regularized versions of matrix completion [51], binary matrix completion [48] and (shallow) matrix factorization [25].…”
Section: Introductionmentioning
confidence: 99%